Bilingual Learning Strategies of Arabic and English: A Perspective of Noam Chomsky's Linguistic Thought - Muhammad Iqbal Hasanuddin; Muhammad Irwan; Muhammad Rusydi; Abd. Muis Said (Newinera Publisher, 2025)
This systematic literature review evaluates Arabic English bilingual strategies through the lens of Noam Chomsky’s Universal Grammar and generative linguistics. By synthesizing 30 high quality studies from an initial 585 records, the review confirms that generative frameworks provide substantial explanatory power for bilingual acquisition. Key findings indicate that L1 Arabic transfer significantly shapes English L2 development, particularly in pro drop and verb raising parameters. While the Full Transfer Full Access model suggests learners retain the ability to achieve native like proficiency, adult learners struggle with parameter resetting when relying solely on positive evidence. Pedagogical implications are profound: explicit instruction using negative evidence and heightened awareness of syntactic differences are essential to reduce interference errors. Additionally, mastering collocations requires targeted focus beyond simple translation equivalence. The review highlights critical research gaps in longitudinal data and child bilingualism, offering vital directions for curriculum design and teacher training.